Medicinal uses of Prosopis juliflora (Sw.) DC. in rural communities from Paraguaná peninsula, Venezuela - Taisma, María Angélica (2017)
This paper provides information on the medicinal uses of Prosopis juliflora (Sw.) DC. in five rural localities of the Peninsula Paraguaná (State Falcon, Venezuela). We realize a survey with semi-structured interviews applied to 51 informants between 23 and 86 years old. All interviewees attributed healing properties to leaves, fruits and / or stems of P. juliflora. The highest percentages of medicinal use of the species referred to orthopedic, ophthalmologic and male sexual function disorders. Some other medicinal uses reported in a lesser extent include treatments for diabetes, digestive system diseases, parasitosis, eruptive diseases, intervening in cases of general malaise, kidney stones and cancer. The results represent the first compilation of medicinal uses of P. juliflora in Venezuela, and allow a foundation for the development of research aimed at determining their pharmacological and biochemical prospection.